Holistic Islamic Education: A Study of the Thought of Imam Al-Ghazali and Muhammad Abduh - Adnan, Irfan Maulana; Marsono, Marsono; Prasetya, Herawan Budi; Faqih, Muhammad Ridwan (Al-Jadwa: Jurnal Studi Islam, 2025)
Islamic education plays a crucial role in shaping a whole human being who is not only intellectually intelligent but also morally upright and spiritually profound. However, modern education often falls into a dichotomy between religious and secular sciences, resulting in moral decline and a weakened spiritual orientation among students. To address these challenges, this study examines the educational thought of Imam Al-Ghazali and Muhammad Abduh within the framework of holistic Islamic education. The aim is to compare Al-Ghazali’s concept of spirituality with Abduh’s rationalism and to explore their relevance in constructing a comprehensive Islamic education system. This research employs a qualitative descriptive method through library research, analyzing classical works of both scholars as well as secondary literature from books and academic journals. The findings reveal that Al-Ghazali emphasizes tazkiyatun nafs (purification of the soul), moral formation, and the integration of knowledge with spirituality. Meanwhile, Abduh promotes educational reform, rationality, and openness to modern sciences through ijtihad. The synthesis of their ideas suggests that ideal Islamic education must harmonize intellect and spirituality, reject the dichotomy of knowledge, and cultivate individuals who are both critical and religious. The contribution of this study lies in offering a conceptual framework for developing a contemporary Islamic curriculum that balances intellectual, spiritual, and moral dimensions.